Development of Interactive Multimedia Motion Graphics Based on Reroroja Mangrove Local Wisdom to Improve Conceptual Understanding of IPAS - Marsela Rinielda Dua; Paula Emerentiana; Maria Vigilina Lena Maran (Postgraduate, University of Mataram, 2025)
This study aims to develop and examine the effectiveness of interactive multimedia motion graphics based on mangrove reroroja local wisdom in enhancing students’ conceptual understanding of IPAS. This research employed the Research and Development (R&D) method using the ADDIE model. The subjects of the study were fourth-grade students and a teacher at SDI Magelo’o. The results of the material expert validation showed a score of 32 with a percentage of 96%, categorized as “highly feasible,” while the media expert validation achieved a score of 33 with 100%, also “highly feasible.” Students’ responses indicated a 100% “strongly agree” category, showing that the multimedia was attractive and engaging. Field testing with 18 students demonstrated a significant improvement in understanding, with pretest and posttest average scores of 45.00 and 96.11, respectively. The N-Gain Score of 0.91 was categorized as “high.” Thus, the motion graphic–based interactive multimedia grounded in mangrove reroroja local wisdom proved to be effective in improving students’ conceptual understanding of IPAS and fostering interest in learning.